2017
DOI: 10.1002/gps.4790
|View full text |Cite
|
Sign up to set email alerts
|

Online assessment of risk factors for dementia and cognitive function in healthy adults

Abstract: Known modifiable risk factors for dementia are associated with cognitive performance in non-demented individuals in late midlife and older age. This provides further support for public health interventions that seek to manage these risk factors across the lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
4
37
0
Order By: Relevance
“…For the current analyses, variables including age, level of education, gender, history of stroke, current depression severity, historical depression severity which is the severity of depressive symptoms during their worst previous depressive episode, and the age of onset of depression were included. These factors were hypothesised as being potentially relevant to cognitive function based on previous studies assessing cognitive function in this cohort …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the current analyses, variables including age, level of education, gender, history of stroke, current depression severity, historical depression severity which is the severity of depressive symptoms during their worst previous depressive episode, and the age of onset of depression were included. These factors were hypothesised as being potentially relevant to cognitive function based on previous studies assessing cognitive function in this cohort …”
Section: Methodsmentioning
confidence: 99%
“…In order to assess baseline cognitive function, the PROTECT study used a validated online cognitive test package containing four tasks: (1) verbal reasoning test (VR), which assesses a combination of grammatical and reasoning skills (executive function); (2) digit span task (DS), which measures verbal working memory by assessing the ability to remember a sequence of numbers; (3) paired associate learning task (PAL), which assesses visuospatial episodic memory; and (4) self‐ordered search test (SOS), which assesses complex visual working memory . Each task was performed online by participants on three occasions during 1 week to provide a baseline assessment.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 This study utilises the PROTECT cohort to examine the association of reported use of word puzzles with cognitive performance. It is a 10-year longitudinal study with annual assessment of cognitive function and other variables, which offers a means of exploring factors which influence cognitive trajectory in later life.…”
Section: Data From the Medical Research Council Cognitive Function Anmentioning
confidence: 99%
“…9,11,13 The outcome measure of each task is the total score of correct responses, which is corrected for errors made. The PCTB assesses aspects of attention and working memory and takes 10 minutes to complete.…”
Section: Cognitive Assessmentmentioning
confidence: 99%
“…[13][14][15] The cohort of over 20 000 adults aged 50 years old and above complete two independent annual online assessments of core aspects of cognitive function and lifestyle behaviours, offering a valuable and evolving dataset of independently validated cognitive variables with which to explore the factors, which influence brain function as we age. [13][14][15] The cohort of over 20 000 adults aged 50 years old and above complete two independent annual online assessments of core aspects of cognitive function and lifestyle behaviours, offering a valuable and evolving dataset of independently validated cognitive variables with which to explore the factors, which influence brain function as we age.…”
Section: Introductionmentioning
confidence: 99%